Analisis Pengaruh Perubahan Beban Generator Terhadap Efsiensi Kinerja PLTU Bosowa Energi Jeneponto Unit 2 - Andreas Pangkung; Herman Nawir; Aditya Nugraha Adji Santoso (Politeknik Negeri Ujung Pandang, 2020)
This study aims to determine the effect of changes in generator load on efficiency performance in steam power plants and to determine the amount of input power in the boiler. Data collection was carried out at PT. Bosowa Energi PLTU Jeneponto. The data are the power output, fuel consumption, and the calorific value of the fuel. Then perform data analysis by calculating input power and efficiency. From the result of the study, the highest efficiency is on May 20, 2018 at 18.00 with a load of 90.00 MW, namely 55.68% and the lowest efficiency is on May 12, 2018 at 03.00 with a load of 64.98 MW, namely 22.69%. The highest boiler input power based on the analysis results was on May 3, 2018 at 20.00, namely 356.61 MW, and the lowest boiler input power based on the analysis was on May 15, 2018 at 07.00, namely 128.14 MW.